Investigação da participação de adrenoceptores α1A e α1D na contração da cauda de epididímo de rato e sua androgênica e estrogênica - Kiguti, Luiz Ricardo de Almeida [UNESP] (2014)
The epididymis is the male reproductive organ responsible for sperm maturation and storage. The contraction of cauda epididymis (CE) during ejaculation is one of the first events of seminal emission phase of ejaculation and the sympathetic nervous system plays a key role in the CE contraction via α1 adrenoceptors (α1-ARs) activation. In this study we show that CE expresses α1A and α1D-ARs and both receptor subtypes contribute in a complex way to the CE contraction induced by α1-ARs agonists. The α1D modulates α1A-ARs induced contraction irrespective of agonist-mediated α1D activation. There is no desensitization of CE α1A-ARs to oxymetazoline. The androgens were shown to play an important role in the maintenance of such α1A/α1D interaction as the androgen deprivation unravels the cryptic functional α1D-ARs. Estrogens had no effect on α1-ARs mediated contraction of CE. The complex α1A/α1D interaction is discussed in the context of receptor heterodimerization as we showed, for the first time, heteromerization of recombinant α1A/α1D-ARs